Impacts of Labor Market Institutions and Demographic Factors on Labor Markets in Latin America - Kugler, Adriana (Washington, D.C. : International Monetary Fund, 2019)
This paper documents recent labor market performance in the Latin American region. The paper shows that unemployment, informality, and inequality have been falling over the past two decades, though still remain high. By contrast, productivity has remained stubbornly low. The paper, then, turns to the potential impacts of various labor market institutions, including employment protection legislation (EPL), minimum wages (MW), payroll taxes, unemployment insurance (UI) and collective bargaining, as well as the impacts of demographic changes on labor market performance. The paper relies on evidence from carefully conducted studies based on micro-data for countries in the region and for other countries with similar income levels to draw conclusions on the impact of labor market institutions and demographic factors on unemployment, informality, inequality and productivity. The decreases in unemployment and informality can be partly explained by the reduced strictness of EPL and payroll taxes, but also by the increased shares of more educated and older workers. By contrast, the fall in inequality starting in 2002 can be explained by a combination of binding MW throughout most of the region and, to a lesser extent, by the introduction of UI systems in some countries and the role of unions in countries with moderate unionization rates. Falling inequality can also be explained by the fall in the returns to skill associated with increased share of more educated and older workers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet